Unravelling the role of biochar-microbe-soil tripartite interaction in regulating soil carbon and nitrogen budget: a panacea to soil sustainability - Bhaskar Jyoti Parasar; Niraj Agarwala (Biochar)
Abstract Global food requirements necessitating enhanced crop productivity have negative consequences such as soil degradation due to acidification and nutrient leaching escalated by excessive application of chemical fertilizers and consequently increasing greenhouse gas emission. This has sought sustainable organic approaches like soil amendment with biochar to mitigate the adverse consequences of these effects, ensuring balanced ecosystem functioning. Reconciling various studies, this review provides a better understanding of the belowground mechanisms decoding multifaceted traits associated with plant and biochar-microbe-soil tripartite interaction, including microbe-mediated regulation of C and N stoichiometry, soil enzyme functioning, regulation of greenhouse gases, soil respiration rate and alteration in abundance of microbial functional genes. Furthermore, this review exclusively gives holistic insights into specific microbes induced by biochar treatment and their role in altering soil C and N dynamics. It attempts to spur in-depth, long-term studies tackling challenges in sustainable agriculture and mitigate environmental issues to achieve C neutrality and N retention, envisaging a healthy soil ecosystem. Graphical Abstract